(untitled) (Fiep Bulletin - online, 2019)
Objective: To analyze the national scientific production on the Family Health Strategy. Methodology: After applying thecriteria of inclusion and in-depth reading of the articles in the total of thirty-two productions, thirteen articles were selected to beanalyzed and demonstrated in three categories. Results: The main ideas of the articles about the host approach in the ESF arepresented in three categories: Reception from the Access point of view; Reception as solving, Access and organization of the systemand Permanent Education. The subject is still little discussed in the scientific productions, especially with regard to integrality in theESF, the most frequent discussions deal with the reception only as access proper and little is said in the resolutiveness. FinalConsiderations: After completing the present study, we can consider that health care has expanded, but there is still a need tosubsidize permanent education actions for FHT teams, reception beyond nursing, specialization courses and residency in Health ofthe Family, optimizing new approaches to the health-disease process.